Understanding Somalia's social contract and state-building efforts: Consequences for donor interventions - Mathieu Cloutier; Hodan Hassan; Deborah H. Isser; Gaël Raballand (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
Building on a World Bank regional study in Africa aiming at measuring social contracts concepts and within the framework of reflecting on future donor interventions, this paper applies social contracts measurement and complements with qualitative assessments in Somalia. This paper uses the framework developed regionally to explore the citizen-state bargain and social outcomes in Somalia and is relevant for most fragile and conflict-affected countries. The qualitative parts describing the social contract in Somalia use the lenses of security, education, and taxes to describe the current setting. It is usually assumed that improved service delivery in fragile states should improve almost automatically state legitimacy and then reduce conflict likelihood. This paper shows that the security imperative prevails in such countries and that tax bargaining hardly exists in most cases. Citizens' expectations are usually low, which explains that how service delivery is improved matters a lot for state legitimacy. This work draws lessons pertaining to past engagement, building on Somalia's history and also reflecting on how aid may impact the country.
Keywords: H26; N47; F52; P45; 330; Somalia; social contract; security; tax; education; legitimacy; conflict